Sensing-throughput tradeoff for interference-aware cognitive radio networks - Kan, Changju; Ding, Guoru; Song, Fei; Wu, Qihui (2012 2nd International Conference on Computer Science and Network Technology, 2012)
Nowadays cognitive radio networks (CRNs) have been proposed as a promising method to solve the problem of radio spectrum shortage and spectrum sensing has been known as a key step to enable the CRNs and utilize the precious spectrum resources. In order to protect primary users from being interfered, most of the related work has focused on the restriction of the probability of missed detection, however in practice, even under the missed detection cases, secondary users located far away from the primary users can also be interference-free to primary users. Motivated by this fact, in this letter we introduce an interference-aware spectrum sensing model and investigate the issue of sensing-throughput tradeoff in interference-aware cognitive radio networks. Specifically, in this letter we take the throughput as the objective of the cognitive radio network, and search for the maximum achievable throughput by jointly optimizing the sensing time and the detection threshold. Compared with the existing algorithms, the accompanying analytical and numerical analysis in this letter show that the proposed algorithm makes better utilization of the spectrum resources. Specially, the proposed algorithm can further improve the achievable throughput of the CRN by raising up to 0.653 bit/s/Hz within the distance of 500m to about 850m which is increased by 48% in average of the achievable throughput and up to 3.208 bit/s/Hz within the distance of 1600m to 2000m which is increased by 49.4% in average.